Arbitration in Agreement Dispute (Perspective of Law Number 30 Year 1999) - Rahmat Ihya; Abdul Qudus Salam; Muh Bangsu; Rohman Hakim; Hermawan Hermawan (Rechtsnormen: Journal of Law, 2023)
Background.  In business relations between the parties in the development does not rule out the possibility of problems that require solutions. Purpose. This research aims to find out the process of resolving civil disputes through the Aribitrase court based on Law Number 30 of 1999 Method. The method in this research uses a normative juridical approach, which means that a study is carried out based on laws and judicial decisions that have permanent legal force. In the collection of legal materials using two ways, namely literature research by reviewing the literature and opinions of legal experts related to research problems. Results. The results of the research can be concluded that the arbitration agreement cannot stand and cannot bind the parties if the arbitration agreement does not coincide with the main agreement, which will be handled by the arbitration agreement is regarding disputes arising from the main agreement, so a civil dispute can be submitted for resolution through the arbitration court if it meets the subjective and objective requirements in the Basic Agreement (JOC). the parties agree that if there is a civil dispute it will be resolved through arbitration. Conclusion. The Arbitration institution has a binding nature on the parties and is final in the sense that the parties cannot appeal to the general court after the Arbitration decision.